Compensation of Wind Generator Power Fluctuations in Microgrid Applications by Superconducting Magnetic Energy Storage - Molina, Marcelo Gustavo (2012)
Grid connection of wind power generation (WPG) is becoming today an important form of distributed generation (DG). The penetration of these DG units into AC microgrids (MGs) is growing rapidly, enabling reaching high percentage of the installed generating capacity. However, the fluctuating and intermittent nature of this renewable generation causes variations of power flow that can bring both power quality and reliability issues to the electrical grid. To overcome these problems, superconducting magnetic energy storage (SMES) arises as a potential alternative to compensate these power flow fluctuations and thus to significantly enhance the MG dynamic security. To this aim, the management of the energy stored in the SMES device is crucial for optimizing the storage capacity as well as for preventing the device from becoming overcharged or uncharged. This paper proposes the use of an improved SMES controller for the stabilization of the fluctuating active power injected into the microgrid by wind generators. In this sense, the design and implementation of a high performance active power controller of the SMES is described. The control is based on fuzzy logic techniques and uses an enhanced fuzzy inference system (FIS) combined with a unique filter block. Moreover, a detailed model of the SMES unit and its power conditioning system (PCS) for connecting to the electric grid is derived. The dynamic performance of the proposed system and its impact on the MG operation is validated by computer simulation.